An Optimal Load Shedding Methodology for Radial Power Distribution Systems to Improve Static Voltage Stability Margin using Gravity Search - Khamis, Aziah (Universiti Teknologi Malaysia, 2014)
Voltage stability is one of the major concerns in operational and planning of modern power system. Many strategies have been implemented to avoid voltage collapse, which the load shedding considered as the last option. However, optimization is needed to estimate the minimum amount to shed so as to prevent voltage instability. In this paper, an effective method is presented for estimating the optimal amount of load to be shed in a distribution system based on the gravitational search algorithm (GSA). The voltage stability margin (VSM) of the system has been considered in the objective function. The optimization problem is formulated to maximize the VSM of the system and at the same time satisfying the operation and security constraints. The optimum solution depends on the predefined constraints such as the number of load buses available to shed and the maximum amount of load permitted to shed. Simulation result conducted on the IEEE 33 bus radial distribution system shows that the system voltage stability can be improved by optimally shedding the loads at critical system buses. The results also indicate that the numbers of load buses available for load shedding does not have a significant impact on voltage stability margin, but it is highly dependent on the maximum amount of load permitted to shed.